2011
DOI: 10.4049/jimmunol.1001672
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Retinaldehyde Dehydrogenase Enzymes in Mucosal Dendritic Cells and Gut-Draining Lymph Node Stromal Cells Is Controlled by Dietary Vitamin A

Abstract: The vitamin A metabolite retinoic acid (RA) plays a crucial role in mucosal immune responses. We demonstrate in this study that RA-producing retinaldehyde dehydrogenase (RALDH) enzymes are postnatally induced in mesenteric lymph node (MLN) dendritic cells (DCs) and MLN stromal cells. RALDH enzyme activity in lamina propria-derived CD103+ MLN-DCs did not depend on TLR signaling. Remarkably, RA itself could directly induce RALDH2 in both DCs and stromal cells in vitro. Furthermore, upon provision of a vitamin A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
153
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(166 citation statements)
references
References 63 publications
11
153
2
Order By: Relevance
“…+ mDCs, but not CD141 high mDCs, express a high level of RALDH2 in response to GM-CSF and VD 3 In search of human DCs that express a high level of RALDH enzymes, different subsets of blood DCs were treated with various factors that have been reported to modulate immunostimulatory activity of DCs (Table I), and ALDH activity was measured with Aldefluor (2,4,5,7,8,12,19). To keep mDCs alive, we added GM-CSF (22) to CD1c + mDCs.…”
Section: Human Blood Cd1cmentioning
confidence: 99%
See 2 more Smart Citations
“…+ mDCs, but not CD141 high mDCs, express a high level of RALDH2 in response to GM-CSF and VD 3 In search of human DCs that express a high level of RALDH enzymes, different subsets of blood DCs were treated with various factors that have been reported to modulate immunostimulatory activity of DCs (Table I), and ALDH activity was measured with Aldefluor (2,4,5,7,8,12,19). To keep mDCs alive, we added GM-CSF (22) to CD1c + mDCs.…”
Section: Human Blood Cd1cmentioning
confidence: 99%
“…It has been shown that CD103 + DCs in lamina propria and mesenteric lymph nodes (MLNs) produce RA and thus to promote the generation of gut-homing regulatory T (Treg) cells (3). GM-CSF (4) and RA (4)(5)(6)(7)(8) are pivotal factors to induce mouse DCs to express retinal dehydrogenase (RALDH)2, which is encoded by the aldehyde dehydrogenase 1 family, member A2 (ALDH1A2) gene and converts retinal to RA. IL-4 (4, 9) and TLR ligands (2,4,5,(10)(11)(12) augment the expression of RALDH2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter still receive multiple input signals from their microenvironment (such as Wnt proteins48) that can shape their capacity to stimulate T cells, and which are often absent or present at non‐physiological levels in in vitro settings. Indeed, the VitA derivative retinoic acid (RA) has a crucial role in DC differentiation: not only does it induce the formation of intestine‐homing pre‐mucosal DC (pre‐μDC) in the bone marrow,49 but it also shapes further differentiation and function in target tissues through its receptor RAR 6, 50, 51, 52, 53. In contrast, a similar role of VD3 and VDR in this context is not known.…”
Section: Vd3 and DC Precursor (Pre‐dc) Derived Dc In The Mousementioning
confidence: 99%
“…Many studies have suggested that CD103 ϩ DCs in the small intestine are responsible for the high level of RA in mesenteric lymph node (MLN) (RALDH2), Peyer's Patch (PP) (RALDH1), and lamina propria (LP) (RALDH2) of the small intestine (84). Recent studies have shown that not only are there more CD103 ϩ DCs in murine small intestine lamina propria (SI-LP) and draining MLN than in other lymphoid tissues, but CD103 ϩ DCs in SI-LP and MLN showed higher Raldh2 expression and activity (132).…”
Section: A Ra Synthesis In the Gutmentioning
confidence: 99%